Physiological factors affecting performance in rowing - Miller, T. F.; Popov, D. V.; Saraev, O. A.; Vinogradova, O. L. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Revealing factors limiting the performance is one of the main tasks in training of elite athletes . Knowing these factors we may find optimal training impacts for increasing athlete`s performance. The aims of our work were to identify physiological parameters, affecting the special performance in rowing and to predict performance using physiological tests. Methods: 298 rowers (open category: 181 men, age 15-38 and 117 women, age 14-37) participated in 14 test sessions. In these test sessions absolute and relative fat and muscle mass, isokinetic force of the knee extensor muscles (angular velocity 300, 240, 180, 60 deg/s), as well as maximum oxygen consumption, oxygen consumption at anaerobic threshold, maximum aerobic power and power at anaerobic threshold were measured. Results of physiological tests were compared with the rowing ergometer (Concept II) 2000 m time trail. Results: Regression analysis revealed that the absolute values of muscle muss, knee-extensors force, maximum aerobic power, power at the anaerobic threshold, maximum oxygen consumption, and oxygen consumption at the anaerobic threshold were significantly associated with the 2000 m time for both men and women. Simultaneous influence of knee-extensors muscle strength and aerobic capacity of organism on 2000 m time trail was evaluated by multiple regression. It was found that the anaerobic threshold had a greater influence on rower`s performance than the knee-extensors muscle strength. Discussion: Our work revealed significant relationships between 2000 m time trail and absolute, but not relative physiological indices. Multiple regression analysis allowed to calculate the individual values of the power at anaerobic threshold and the knee-extensors strength required to achieve a desired result/2000 m time trial.